2018
DOI: 10.1111/bju.14372
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures prognostic for relapse in stage I testicular germ cell tumours

Abstract: Objectives To identify differentially expressed genes between relapsed and non‐relapsed clinical stage I testicular germ cell tumours (TGCTs). Materials and Methods We reviewed patients with clinical stage I non‐seminoma and seminoma from an institutional database (2000–2012) who were managed by active surveillance. Patients with non‐relapsed non‐seminoma and non‐relapsed seminoma were defined as being relapse‐free after 2 and 3 years of surveillance, respectively. RNA extraction and gene expression analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Korkola et al identified an eight-gene model that can predict overall survival in patients with TGCTs in 2009, but without validation of RFS ( 34 ). Lewin et al also reported a discriminatory gene expression profile between relapsed and non-relapsed cases on the basis of 10- and 30-gene signatures ( 35 ). However, the prediction score by Lewin et al was limited to a cohort with single histology and lacked validation in large external sets.…”
Section: Discussionmentioning
confidence: 99%
“…Korkola et al identified an eight-gene model that can predict overall survival in patients with TGCTs in 2009, but without validation of RFS ( 34 ). Lewin et al also reported a discriminatory gene expression profile between relapsed and non-relapsed cases on the basis of 10- and 30-gene signatures ( 35 ). However, the prediction score by Lewin et al was limited to a cohort with single histology and lacked validation in large external sets.…”
Section: Discussionmentioning
confidence: 99%
“…Validate of hub molecules. The expression patterns of three types of molecules (TF, miRNA and gene) identified as hubs were evaluated using an independent dataset from GEO (ID: GSE99420) 62 . The original study was to find gene signatures for relapse after 2 and 3 years of surveillance of TGCT.…”
Section: Methodsmentioning
confidence: 99%
“…S4, and Table 4. Since these hub genes in top 5 FFLs were important for the regulatory mechanism of TGCT, we evaluated their regulatory patterns using a validation dataset (GEO GSE99420) 62 below.…”
Section: Common and Subtype-specific Regulatory Network Topologicalmentioning
confidence: 99%
“…Chang et al evaluated the expression patterns of cancer-testis (CT) genes of TGCT patients in TCGA, and confirmed the role of CT genes in the prognosis of TGCT (51). By retrospectively analyzing the characteristics of patients with stage I TGCT, Lewin identified the differential gene expression profile between patients with relapsed and nonrelapsed TGCT (52). Mallik and his colleagues combined analysis of gene expression and methylation in seminoma and non-seminoma, providing a co-regulation research perspective (13).…”
Section: Discussionmentioning
confidence: 98%